2022
DOI: 10.3389/ffgc.2022.953130
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intercept trap fluids and aerial spore collectors to survey fungal spores

Abstract: Surveillance for early detection of non-native, invasive pathogens requires simple, sturdy, and easy-to-use collecting devices. In this study, we compared the fungal species detected in wet collection cups of Lindgren traps vs. those detected on slides with oiled cheesecloth as aerial spore collectors. DNA was extracted and amplified from both using the primers ITS1F and gITS7, and Illumina sequencing was used for the metabarcoding of fungi present in samples. In 90 samples, there were 1,277 fungal operational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Our results do, however, substantiate the utility of preservative fluids for forest surveillance activities. This substrate provides a consistent and stable source from which to sample when targeting fungi and other microbes, allowing for standardization of an approach that extends beyond only screening for insect-vectored pathogens (Berube et al, 2022). While both the anti-freeze and glycol mixtures used in the current study showed no apparent difference in their efficacy for long-term storage (>300 days at 4 • C), further investigation is needed to test for within sample differences that might exist for these substrates.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Our results do, however, substantiate the utility of preservative fluids for forest surveillance activities. This substrate provides a consistent and stable source from which to sample when targeting fungi and other microbes, allowing for standardization of an approach that extends beyond only screening for insect-vectored pathogens (Berube et al, 2022). While both the anti-freeze and glycol mixtures used in the current study showed no apparent difference in their efficacy for long-term storage (>300 days at 4 • C), further investigation is needed to test for within sample differences that might exist for these substrates.…”
Section: Discussionmentioning
confidence: 97%
“…Considering that the traps are currently used to monitor insect pests, our methodology focused on speed, scalability, and compatibility for targeting phytopathogens, and consequently incorporated non-destructive approaches when working with the insect specimen subsamples. Previous studies have established that semiochemical-baited insect traps are effective for fungal surveillance, whether sampling the preservative fluids alone (Tremblay et al, 2018(Tremblay et al, , 2019Berube et al, 2022) or through destructive sampling of the insect-specimens (Malacrino et al, 2017;Miller et al, 2019;Rassati et al, 2019). To our knowledge, however, the impact on recovering targeted fungi from insect trap subsamples (i.e., extracting from preservative fluids vs. insect specimens) is yet to be assessed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations